Domestic violence and school performance of children and adolescents - Pereira, Tatiana Cristina; Pucci, Silvia Helena; Armond, Jane (Brazilian Journal of Global Health, 2021)
OBJETIVO: A presente pesquisa buscou verificar se existe relação entre a violência doméstica e o desempenho escolar de crianças e adolescentes, como são as relações interpessoais no contexto familiar, quais os tipos de violência doméstica frequentes e o desempenho escolar de crianças e adolescentes vitimizados/não vitimizados. MÉTODOS: Foi realizado um estudo transversal, no qual os dados foram coletados por meio de um Questionário de Caracterização Sociodemográfico e do Inventário de Questões para o Diagnóstico de Violência Doméstica em Crianças e Adolescentes, elaborados para esta pesquisa. Foram atendidos todos os princípios éticos preconizados em pesquisas que envolvem seres humanos, garantindo o sigilo e a confidencialidade dos dados obtidos. RESULTADOS: A apreciação dos dados sugere que a Violência Doméstica está relacionada com o nível de desempenho escolar de crianças e adolescents. Além disto, o tipo de violência doméstica identificado nesta população foi a verbal/psicológica. Sobre o desempenho escolar, a amostra apresentou resultados medianos e abaixo da média. CONCLUSÃO: A violência doméstica pode impactar no desempenho escolar de crianças e adolescentes. A amostra de sujeitos estudada, permite refletir a cerca do silêncio que assola a sociedade, quando se aborda a temática da violência doméstica contra crianças e adolescentes em seus múltiplos contextos, sobretudo no espaço escolar e no ambiente familiar. DESCRITORES: Violencia, Violência doméstica, Desempenho escolar, Crianças, Adolescentes. ABSTRACT OBJECTIVE: The current study aimed to establish if there is a relationship between domestic violence and school performance of children and adolescents, through verification of the interpersonal relationships in the family context, the most frequent types of domestic violence, and the school performance of victimized/non-victimized children and adolescents. METHODS: A cross-sectional study was carried out, in which data were collected through a Sociodemographic Characterization Questionnaire and the Inventory of Questions for the Diagnosis of Domestic Violence in Children and Adolescents, which was developed for this study. All ethical principles recommended in research involving human beings were complied with, ensuring the secrecy and confidentiality of the data obtained. RESULTS: The analysis of the data suggests that Domestic Violence is related to the level of school performance of children and adolescents. In addition, the type of domestic violence identified in this population was verbal/psychological. Regarding school performance, the sample attained average and below average results. CONCLUSION: Domestic violence can impact the school performance of children and adolescents. The sample of subjects studied enables us to reflect on the silence that plagues society when addressing the issue of domestic violence against children and adolescents in its multiple contexts, especially in the school space and in the family environment. DESCRIPTORS: Violence, Domestic violence, School performance, Children, Adolescents.